Transhumanizem, posthumanizem – izziv (krščanskemu) ekofeminizmu - Furlan-Štante, Nadja (Monitor ISH, 2021)
: This article compares the (Christian) ecofeminist ethic of relationality - the interconnectedness of all beings (human and natural non-human) in the web of life (interconnected subjectivity) - with the transhumanist ethic of human enhancement and technological singularity. Moreover, a critique of transhumanism and its possible) abuse of technological power - over humanity and nature - is elaborated, as the “new” superintelligence could drive accelerated technological progress and leave ecofeminist ecocentric egalitarianism behind, while moving towards posthumanism as a goal.
Keywords: ekologija; etika; feminizem; filozofija; Humanizem; Krščanstvo; tehnološki razvoj